Traumatic Spinal Cord Injury, an Overview of Epidemiology and Management in Vindhya Region (Indian Journal of Public Health Research & Development, 2021)
Background: Traumatic spinal cord injury (SCI) is a life changing neurological condition with substantialsocioeconomic implications for patients and their care-givers. Recent advances in medical management ofSCI has significantly improved diagnosis, stabilization, survival rate and well-being of SCI patients.Objectives: The objectives of this study were (1) to determine the characteristics of patients sustaining spinaltrauma in India and (2) to explore the association between patient or injury characteristics and outcomesafter spinal trauma.Method: The study includes patients admitted with TSCI admitted at the Central shyam shah memorialmedical college and associated government medical college, from March 2019 to March 2020. Patientenrolled for the study were admitted directly or after being referred from peripheral health centers. Bothconservatively managed and operated patients were taken into accountResults: Most patients were middle-aged (mean age = 51.0 years; median age = 55.5 years; range = 18.0to 72.0 years), male (60.4%), injured from falls (72.4%), and treated in a private setting (59.9%). Fracturesin the lumbar region (51.0%) were most common, followed by thoracic (30.7%) and cervical (18.2%).More than 1 in 5 (21.6%) patients experienced a treatment delay greater than 24 hours, and 36.5% arrivedby ambulance. Thirty-day mortality and complication rates were 2.6% and 10.0%, respectively. Care inthe public hospital system (odds ratio [OR] = 6.7, 95% CI = 1.1-41.6), chest injury (OR = 11.1, 95% CI =1.8-66.9), and surgical intervention (OR = 4.8, 95% CI = 1.2-19.6) were independent predictors of majorcomplications.Conclusions: Treatment in the public health care system, increased severity of injury, and surgicalintervention were associated with increased risk of major complications following spinal trauma. The needfor a large-scale, prospective, multicenter study taking into account spinal stability and neurologic status isfeasible and warranted.
Keywords: Spinal trauma, spinal fracture, India, complications, reoperation, mortality, public versus private hospitals, spinal surgery